An integrated approach to cardioprotection in lymphomas. Issue 6 (June 2022) - Maraldo, Maja V; Levis, Mario; Andreis, Alessandro; Armenian, Saro; Bates, James; Brady, Jessica; Ghigo, Alessandra; Lyon, Alexander R; Manisty, Charlotte; Ricardi, Umberto; Aznar, Marianne C; Riccardo Filippi, Andrea
Summary: In potentially curable cancers, long-term survival depends not only on the successful treatment of the malignancy but also on the risks associated with treatment-related toxicity, especially cardiotoxicity. Malignant lymphomas affect patients at any age, with acute and late toxicity risks that could have a severe effect on morbidity, mortality, and quality of life. Although our understanding of chemotherapy-associated and radiotherapy-associated cardiovascular disease has advanced considerably, new drugs with potential cardiotoxicity have been introduced for the treatment of lymphomas. In this Review, we summarise the mechanisms of treatment-related cardiac injury, available clinical data, and protocols for optimising cardioprotection in lymphomas. We discuss ongoing research strategies to advance our knowledge of the molecular basis of drug-induced and radiation-induced toxicity. Additionally, we emphasise the potential for personalised follow-up and early detection, including the role of biomarkers and novel diagnostic tests, highlighting the role of the cardio-oncology team.